Hemangioblastoma, a rare tumor of supratentorial and infratentorial regions: A report of two cases with review of literature - Shivam Chakraborty; Chhanda Das; Mamata Guha Sinha (Annals of Medical Science and Research)
Hemangioblastoma (HBL) is a rare benign neoplasm arising from the vascular stromal cells. It is a WHO Grade 1 neoplasm with solid and cystic components. In majority of the cases, it is a sporadic tumor, and in few cases, association with Von Hippel–Lindau syndrome has been found. Here, we present two separate cases of intracranial HBL. One tumor is from the supratentorial region and another one is from the infratentorial region. Although infratentorial HBL is commonly found, supratentorial HBL is very rare. Microscopical similarity with metastatic clear cell renal cell carcinoma can be a diagnostic pitfall.